Analysis Of Financial Performance of Depok City Government - Halimah, Imar (Universitas Pamulang, 2022)
This study aimed to determine the financial performance of the Depok City Government in 2016 and 2017. The data used in this study is the 2017 financial report, then analyzed using the ratio of independence and compatibility. The results of the analysis state that the financial performance of the Depok City Government in the aspect of independence in 2016 was 59%, and in 2017 has increased by 74%; this is included in the sedan category. Meanwhile, from the aspect of compatibility, it is not good in indirect expenditure, namely in 2016 by 25% and 2017 by 28.6%. In contrast, direct expenditure is likely reasonable in 2017, namely 54.4%, compared to 2016, only 49.5% in the poor category. The Depok city government is expected to strive to further increase its PAD by optimizing resource management and expanding sectors with the potential to increase PAD so that it does not depend on revenue from the Central Government.